2016
DOI: 10.1371/journal.pone.0151420
|View full text |Cite
|
Sign up to set email alerts
|

Specific Activation of A3, A2A and A1 Adenosine Receptors in CD73-Knockout Mice Affects B16F10 Melanoma Growth, Neovascularization, Angiogenesis and Macrophage Infiltration

Abstract: CD73 (ecto-5'-nucleotidase), a cell surface enzyme hydrolyzing AMP to adenosine, was lately demonstrated to play a direct role in tumor progression including regulation of tumor vascularization. It was also shown to stimulate tumor macrophage infiltration. Interstitial adenosine, accumulating in solid tumors due to CD73 enzymatic activity, is recognized as a main mediator regulating the production of pro- and anti-angiogenic factors, but the engagement of specific adenosine receptors in tumor progression in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…Our results were demonstrated that CD73‐targeting in the tumor microenvironment through an application of the CD73 siRNA‐loaded NPs could potently suppress the tumor growth, increase the mice survival‐time, and enhance anti‐tumor immune responses (Jadidi‐Niaragh et al, ). Regarding the importance of angiogenesis in the tumor progression and initiation of metastasis and the key function of the adenosine in the angiogenesis (Koszałka et al, ; Sorrentino, Miele, Porta, Pinto, & Morello, ), we examined the anti‐angiogenic potential of our previous therapeutic approach (Jadidi‐Niaragh et al, ) in the tumor‐bearing mice in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were demonstrated that CD73‐targeting in the tumor microenvironment through an application of the CD73 siRNA‐loaded NPs could potently suppress the tumor growth, increase the mice survival‐time, and enhance anti‐tumor immune responses (Jadidi‐Niaragh et al, ). Regarding the importance of angiogenesis in the tumor progression and initiation of metastasis and the key function of the adenosine in the angiogenesis (Koszałka et al, ; Sorrentino, Miele, Porta, Pinto, & Morello, ), we examined the anti‐angiogenic potential of our previous therapeutic approach (Jadidi‐Niaragh et al, ) in the tumor‐bearing mice in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Other antitumour mechanism of dCF could be related with the modulation of angiogenesis, an important aspect in tumour growth. Even though adenosine is known as a proangiogenic factor, dCF treatment increased the percentage of tumour necrosis while reducing tumour size in 4T1 mouse model, suggesting down‐regulation of tumour vascularization. As the effect of dCF on endothelial cell migration in vitro was minor, other antiangiogenic mechanisms should be considered, for example the inhibition of macrophage induced angiogenesis …”
Section: Discussionmentioning
confidence: 99%
“…However, the results are controversial. It has been documented that the A1R agonist could inhibit cell proliferation in colonic cancer, astrocytoma and melanoma cells [9, 10, 17]. In contrast, several studies also showed that the A1R antagonists could reduce cell proliferation [13, 18].…”
Section: Discussionmentioning
confidence: 99%